REASONS OF RAISING THE CONCEPT “MAN” IN ENGLISH PHRASEOLOGY (British Journal of Global Ecology and Sustainable Development, 2022)
In the article reasons of raising the concept “man” in english phraseology. He noted that strengthening the aspiration of young people to science, supporting the initiatives of entrepreneurs, the development of cooperation with foreign countries in various fields will continue to be at the center of reforms.